Meningkatkan Kemampuan Berbahasa Anak Usia Dini Melalui Model Pembelajaran Audio Visual Berbasis Android - Farid Helmi Setyawan (Universitas Trunojoyo Madura, 2016)
Language skills are the abilities, skills, wealth greeting human thoughts and feelings through sound arbitrator, used to work together, interact, and identify themselves in a good conversation. In this study a problem Is the Audio Visual Learning Model-Based Android can improve Proficiency in Early Childhood Group A. The purpose of this study was to determine the improvement of language skills of early childhood through audio visual media in group A . The design of this research is a Class Action Research with research subjects are 12 children in PAUD Nawakartika Beran village District of Ngawi in the academic year 2016/2017. Technique of collecting Data are used such as observation, documentation and questionnaires. Classroom action research on learners' class A, it can be concluded that the audio visual media can improve language skills, it is shown that indicator of increased mastery learning students is increasing from the first cycle (50%) and cycles II (83.3%). Improved performance indicators can be shown by the child is able to interact with their peers using the newly acquired language, liveliness children in participating in learning activities increased significantly, the atmosphere of teaching and learning activities are very conducive. Teacher is advised be able to develop audio-visual media more varied and fun for children.